DIGESTIBILIDAD DEL CAMOTE Y SU EFECTO SOBRE LA DIGESTIBILIDAD DE CONCENTRADOS USADOS EN LA ALIMENTACIÓN DE PERROS - Matute G., Lucero (2003)
Five adult dogs maintained in individual cages were used in an experiment under a 5x5 Latin Square design, to evaluate the in vivo digestibility of the sweet potato, and its effects on the digestibility of commercial dog food. The treatments were T0: 100% concentrated, T25: 25% sweet potato and 75 % concentrated, T50: 50% sweet potato and 50% concentrated; T75: 75 % sweet potato and 25 % concentrated, and T100: 100% sweet potato. Animals were fed at 08:00 hours and feces were previously collected. Proximal analysis of feces and diets were carried out. Each period in the study included 7 days of adaptation and 5 days of control. The digestibility of the dry matter was increased when the sweet potato increased in the ration (p<0.05). The apparent digestibility of the crude protein and the digestibility of the ethereal extract diminished when the sweet potato levels were increased (p<0.05). This study showed that the sweet potato has a high digestibility and significantly affects the digestion of nutrients in the dog. An increase of sweet potato increases the digestion of dry matter and energy, but affects the digestibilidad of the crude protein and the ethereal extract.